ARTIFICIAL DEFOLIATION ON Eucalyptus benthammii AND Eucalyptus dunnii FOR SIMULATION OF LEAF-CUTTING ANT ATTACKS - Nickele, Mariane Aparecida; Reis Filho, Wilson; Penteado, Susete do Rocio Chiarello; Queiroz, Elisiane Castro de (Floresta, 2023)
The effects of different defoliation levels caused by leaf-cutting ants have not yet been evaluated in Eucalyptus benthammii Maiden et Cambage and Eucalyptus dunnii Maiden plants. The aim of this study was to evaluate the losses caused by different defoliation levels on E. benthammii and E. dunnii plants artificially defoliated 30 days after planting, simulating Acromyrmex attacks. Four treatments were evaluated: 0: control, 1: 50%, 2: 75%, and 3, 100% defoliation. Plant height and diameter were recorded at 6, 12, 24, 36 and 72 months after planting. At six months, height and diameter of E. bentammii plants subjected to 100% defoliation differed significantly from control plants, however no significant differences in plant height and diameter were seen after 12 months. In E. dunnii, 100% defoliation resulted in significant plant mortality, and plants that survive this level of defoliation had significant losses in their development. In case of Acromyrmex attack on eucalyptus plants at 30 days after planting, it is suggested to replant E. dunnii 100% defoliated to avoid losses in the end of the forest cycle. In E. benthammii plantations, it is suggested to evaluate the vigor of the 100% defoliated seedlings, as they can recover over time. Only 100% defoliation can lead to losses in Eucalyptus plant growth. However, regionalized studies are necessary to assess the losses that intense defoliation can cause in each situation and in each plant species, as some species, such as E. benthammii, can recover along time.